No benefit of hydrocortisone, ascorbic acid, and thiamine in reducing mortality in adult sepsis patients: a systematic review and meta-analysis - Qing Zhao; Jianguo Xiao; Hui Liu (Emergency and Critical Care Medicine)
Abstract. Background. Supplementation of corticosteroid, ascorbic acid and thiamine in adult septic patients remains controversial. We aimed to evaluate the efficacy and safety of hydrocortisone, ascorbic acid and thiamine (HAT) in adult septic patients. Methods. Data search included Pumbed, EMBASE, and the Cochrane Library from inception to Sep, 2021. Only studies with classifications of sepsis and intravenous HAT treatment were included. Adult patients with sepsis (aged ≥18 years) were divided into 2 groups. The treatment group received HAT therapy, whereas the control group received standard care and/or intravenous hydrocortisone. The primary outcome was hospital mortality. Results. Eleven studies including 4579 patients who fulfilled the predefined criteria were analyzed (6 randomized controlled trials [RCTs] and 5 clinical cohort studies). No hospital mortality reduction was demonstrated in patients treated with HAT when compared to the reference (OR: 0.99; 95% CI: 0.77 to 1.27; I2 = 39%) group. Sequential organ failure assessment (SOFA) score decrement at 72hours was more significant in HAT-treated patients (mean difference [MD]: –1.23; 95% CI: –1.94 to –0.53; I2 = 81%). There was no difference in the duration of vasopressor use between HAT-treated patients and controls (MD: –4.92; 95% CI: –24.38 to 14.53; I2 = 97%). Statistical heterogeneity was noted with no sign of significant publication bias. Conclusion. In adult sepsis and septic shock patients, HAT treatment failed to reduce mortality or shorten vasopressor duration, but reduced SOFA scores.